Pemberdayaan Masyarakat Kampung Rempang Cate Melalui Pelatihan Pemasaran Digital untuk Produk Unggulan Pasir Panjang - Evaliata Br Sembiring; Fandy Neta; Muhammad Nashrullah; Adhitomo Wirawan; Liony Lumombo (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2019)
Riau Islands, which are identical with the fishermen's profession for the people, has the potential to process marine products into superior products. One area that work as a fisherman is Kampung Rempang Cate. This village is located in Galang sub-district, Batam City. Fish catches are processed into food and souvenirs such as fish crackers, rose cakes, lung crackers, empek-empek and others. This village has internet so that people can access social media, but it has not been fully utilized in the economic field. Social media can be used as a media for promoting products and has the potential to improve the economy of the community. Bad weather sometimes happens, causing fishermen not possible to go to sea. When this happens, people can process resource from the sea into food or souvenir that can be sold to other regions such as Batam City through digital marketing. The purpose of this community engagement is to provide training on how to promote products from fish catches and other resources through digital marketing. The community no longer needs to sell processed products directly to Batam City, with no small costs and uncertain buyers. The current positive impact that has been seen is the increase in people's knowledge and insights into digital marketing and improving the community's economy from the implementation of activities.